Physical Activity On Early Childhood Brain Growth - Yanti, Nursaida; Munisa; Rahayu Dwi Utami; Nurhasanah Bakhtiar; Ulfa Mahira; Ika Sasmita (ASIAN PUBLISHER, 2024)
Physical activity in early childhood has a significant influence on brain growth and development. This study used a descriptive qualitative research method with a literature study to evaluate the impact of physical activity on various aspects of child development, such as motor skills, emotions, and the immune system. The results showed that regular and routine physical activity can improve motor skills, as well as strengthen children's immune system. In addition, physical activities that are tailored to the age and ability of the child and supported by a conducive environment can help maximize the potential of children's brain growth and development. Therefore, education and support from parents, educators, and communities in promoting active lifestyles for children is essential to support children's optimal health and development.